Numerical Modeling, Simulation and Validation of Hybrid Solar Photovoltaic, Wind Turbine and Fuel Cell Power System - Sami, S.; Icaza, D. (Journal of Technology Innovations in Renewable Energy, 2015)
The energy conversion equations describing the total power generated by a hybrid system of solar photovoltaic, wind turbine, fuel cell as well as hydrogen storage were presented, and integrated simultaneously. For the purpose of validating, this simulation model, the aforementioned equations were coded with MATLAB V13.2 and used for optimization and design purposes. A block diagram approach was used during the simulation with MATLAB. In order to validate and tune up the predicted output results, on-site data was used to validate the simulation program under various conditions. Comparison between the data and predicted results showed a fair agreement.